Effect of Overweight and Obesity on menstrual cycle in adolescence - رجب, رجاء (Latakia University Journal -Medical Sciences Series, 2023)
Background The prevalence of adolescent obesity has increased significantly worldwide. Adolescent obesity is associated with increased menstrual disorders, which causes complications such as infertility, endometrial cancer, and pregnancy complications. Objective: to determine the prevalence of menstrual disorders among adolescent girls, to study the effect of overweight and obesity on the menstrual cycle in adolescent girls, to identify other risk factors for menstrual disorders among adolescents. METHODS: A cross-sectional study of 164 adolescents answered questions about menstrual cycle, Family status, weight, height, puberty, cigarettes-smoking, physical activity. We studied the effect of overweight and obesity on each parameter of the menstrual cycle individually and then with the combination of other factors (age, smoking, puberty, family status, and physical activity). Results: The age of the participants 13 - 21 years (1.8 ± 19). 25% were smokers. 17.7% overweight. 5.5% obese. 41.5% suffered from an irregular menstrual cycle. 4.3% oligomenorrhea. 3.6% polymenorrhea. 26.8% suffered from menorrhagia, 21.9% metrorrhagea. 45.7% of dysmenorrhoea. overweight has increased the risk of menorrhagia (pvalue 0.048) and metrorrhagea (value < 0.001). in addition to overweight, other risk factors for menorrhagia were physical inactivity (pvalue 0.002) and early puberty (pvalue 0.035). in addition to overweight, physical activity was risk factor for metrorrhagea (pvalue 0.013). Obesity is a risk factor for oligomenorrhea (pvalue 0.006). Conclusion: The prevalence cigaretten-smoke among female adolescents in our study is high compared to international prevalence as well as to neighboring countries. Obesity is a risk factor for oligomenorrhea. overweight is a risk factor for (menorrhagia and metrorrhagia). physical activity is a risk factor for (menorrhagia and metrorrhagia). Also, early puberty is a risk factor for (menorrhagia). Keywords: primary dysmenorrhea, menorrhagia, physical activity